THE EFFECT OF PROJECT BASED LEARNING MODELS ON STUDENT CREATIVITY IN ENVIRONMENTAL POLLUTION MATERIALS - Fatemah Rosma; Mauizah Hasanah (Jurnal Biologi Sains dan Kependidikan, 2021)
The creativity of students in Indonesia is still low compared to other countries. The low of biological creativity is caused by the use of less constructivist learning methods or models. This research was conducted to determine and describe the effect of project based learning on student creativity on environmental pollution material at MAN Model, Banda Aceh. This study used a quantitative descriptive approach with a quasi-experimental design through a one shot case study design. The population in this study were all students of class X MAN Model Banda Aceh with samples taken were students of class X IPA 2. The sample selection used purposive sampling technique. Moreover, the collecting data in this study used a creativity assessment observation sheet. Meanwhile, data processing applied a one-sample t-test statistic (one sample t-test). Based on the results of the t test, it is found that tcount = 50.08 and ttable = 2.04, so tcount (50.08) ttable (2.04). This shows that if tcount ttable, then Ha = accepted, whereas if tcount ttable, then H0 = accepted. Significant levels are ? = 0.05 and dk (n-1). Therefore, because tcount ttable, then Ha is accepted. In conclusion, the alternative hypothesis (Ha) which states that Project Based Learning affects students creativity in environmental pollution material is accepted.